Wooden furniture purchasing system - Nor Asikin, Othman Basir (2005)
Nowadays, Business Industry faced with many competitions, it is becoming more essential for companies to provide a good service.Mostly in small and medium company such as furniture company, all the management activities especially in purchase order are done completely manually.There have faced many problems using manual system such as to read other person handwriting,to keep data and to calculate a large number of orders in short time.The potential to lost or damage and misplace data is high.Therefore,Wooden Furniture Purchasing System is asuggestion system to solve the problem. There are have three(3)sub-modules that had defined to develop for this system such as data information module,purchase order module and purchase invoice.The purpose of developed this system is to computerize all the data.Besides,the company is able to keep and save data more systematic and efficiency.This system also can make a fast calculation although have a large number of orders and able to give suggestion in choose supplier company to order.This system is developed based on Rapid Application Development (RAD) where this type of process model is suitable to apply for the short time of development.Microsoft Visual Basic Version 6.0 Professional Edition and Microsoft Access 2003 is used to developed the system.Using the Wooden Furniture Purchasing System, company can be enchancing their management activities.